METHOD FOR REFINING CRUDE SILICON MELTS USING A PARTICULATE MEDIATOR - KONRAD MAUTNER; KARL-HEINZ RIMBCK (2024)
The subject matter of the invention is a process for oxidatively refining a crude s i l i con melt in the preparation of industrial-grade silicon , i n which process during the refining stage a fine-partic l e mediat or with a particle s i ze parameter dso of between 1 a nd 200 mis added t hat contains a minimum content of metal l urgical si l icon of 8 mass% and at least one or more of t he element s H, C, 0 , F, Cl , Ca , Fe and Al, the fine-particle mediator being added to the crude silicon melt by pneumatic delivery using a gas .